2012
DOI: 10.5392/jkca.2012.12.09.408
|View full text |Cite
|
Sign up to set email alerts
|

Change of Physical Self-concept according to Taekwondo Discipline

Abstract: The purpose of this study was to verify differences in changes of physical self-concept between Taekwondo participation group and non Taekwondo participation group in order to meet the needs of the study the limitations of previous studies had to be considered. The participants were elementary students in S city selected by this researcher. 30 students were in the Taekwondo participation group and 40 students were in the non Taekwondo participation group decided by ACSM(15) exercise guide line standard, three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The study area was divided into China and Korea, and the age groups were classified as children, adolescents, and adults, based on the characteristics of the study participants reported in the included studies. Six of the studies employed the PSDQ as the measurement instrument (Kang & Park, 2003; Lee, 2017; No & Kang, 2014; Peng et al, 2009; Wu, 2014; Zhang & Xu, 2012), while the remaining three studies used modified versions of the PSDQ to suit the characteristics of different study participants (Kim, 2008; Lim & Kim, 2012; Sung, 2009). Hence, the measurement instruments were divided into (a) PSDQ and (b) modified PSDQ.
Figure 1.PRISMA 2020 Retrieval Flow.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study area was divided into China and Korea, and the age groups were classified as children, adolescents, and adults, based on the characteristics of the study participants reported in the included studies. Six of the studies employed the PSDQ as the measurement instrument (Kang & Park, 2003; Lee, 2017; No & Kang, 2014; Peng et al, 2009; Wu, 2014; Zhang & Xu, 2012), while the remaining three studies used modified versions of the PSDQ to suit the characteristics of different study participants (Kim, 2008; Lim & Kim, 2012; Sung, 2009). Hence, the measurement instruments were divided into (a) PSDQ and (b) modified PSDQ.
Figure 1.PRISMA 2020 Retrieval Flow.
…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the different dimensions of physical self-concept, the PSDQ is characterized by 11 dimensions, including physical fitness, physical coordination, physical activity, physical obesity, athletic ability, appearance, strength, flexibility, endurance, physical self-esteem, and overall physical self. However, two of the three studies that employed the modified PSDQ version excluded appearance and physical self-esteem (Kim, 2008; Lim & Kim, 2012). Meanwhile, among the six studies utilizing the original PSDQ, three demonstrated no significant effect of taekwondo on appearance (Lee, 2017; Peng et al, 2009; Wu, 2014), and three showed no significant effect on physical self-esteem (No & Kang, 2014; Peng et al, 2009; Wu, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations